2014
DOI: 10.2138/am.2014.4674
|View full text |Cite
|
Sign up to set email alerts
|

Visible and short-wave infrared reflectance spectroscopy of REE fluorocarbonates

Abstract: An understanding of the mineralogy and petrogenesis of rare earth element deposits has significant implications for their economic viability. Lanthanide-bearing compounds are known to produce sharp absorption features in the visible to short-wave infrared region (VIS-SWIR), however, a significant knowledge gap exists between the fields of hyperspectral reflectance spectroscopy and rare earth element mineralogy. Reflectance spectra were collected from four bastnäsite samples, two parisite samples, and one synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 23 publications
3
37
0
1
Order By: Relevance
“…Reflectance spectra of all carbonatite samples show carbonate absorption features that are typical for calcite at 2.34 µm [34,35]. Rowan et al [11] and Turner et al [33] showed that narrow absorption bands in the VNIR-and SWIR-range are related to specific REE-elements (mostly Nd, e.g., 0.741 and 0.798 µm [33]). The lower detection limit for Nd 3+ in high albedo samples is about 300 ppm [11].…”
Section: Carbonatitementioning
confidence: 93%
See 2 more Smart Citations
“…Reflectance spectra of all carbonatite samples show carbonate absorption features that are typical for calcite at 2.34 µm [34,35]. Rowan et al [11] and Turner et al [33] showed that narrow absorption bands in the VNIR-and SWIR-range are related to specific REE-elements (mostly Nd, e.g., 0.741 and 0.798 µm [33]). The lower detection limit for Nd 3+ in high albedo samples is about 300 ppm [11].…”
Section: Carbonatitementioning
confidence: 93%
“…Names and the location of exploration sectors are also indicated. Coordinate system: WGS 84/UTM 33S; (e) Reflectance spectra of carbonatite sample NA-Epembe-Sec B from the northern high-grade zone with distinct absorption in the VNIR due to Nd 3+ [33]; (f) Reflectance spectra of carbonatite sample NA-14-08-18-B10. Absorption features are marked at 0.741 and 0.798 µm for Nd 3+ , 2.2 µm for Al-OH, 2.3 µm (and 2.5 µm) for Mg-OH and 2.34 µm for calcite.…”
Section: Carbonatitementioning
confidence: 99%
See 1 more Smart Citation
“…In both example spectra, the absorption bands at ~580 nm, ~740 nm, ~800 nm, and ~870 are resolved. These bands are attributed to neodymium based on the publications of [5,16,17,[20][21][22]. Figure 1.…”
Section: Introduction To Imaging Spectroscopy Principles For the Clasmentioning
confidence: 97%
“…Two reference spectra for monazite (a neodymium-bearing mineral) and a monazite-rich rock sample (a calcitic carbonatite from the Fen complex). The key spectral characteristic absorption bands in the VNIR range that are associated with neodymium [5,16,17,[20][21][22]. The graph is modified after Boesche et al 2014 [23].…”
Section: Introduction To Imaging Spectroscopy Principles For the Clasmentioning
confidence: 99%